A quasi-three-dimensional thermal model for multi-stream plate fin heat exchangers. (5th July 2019) - Niroomand, R.; Saidi, M.H.; Hannani, S.K.
Highlights: A quasi three-dimensional modeling of multi-stream plate fin heat exchanger. Consideration of transverse heat conduction through fins. Consideration of heat leakages and inlet mass flow rate maldistribution. Ability to simulate cross flow heat exchangers. Abstract: In this study, a novel pseudo-three-dimensional model is developed to find out both fluid and solid temperature distributions in multi-stream plate fin heat exchangers. In this simulation algorithm, heat exchangers can be in either parallel flow or cross flow configuration. The model considerations include: heat leakage of cap plates and side plates, conduction throughout the solid matrix of the heat exchanger, variable physical properties, and inlet mass flow rate maldistribution. Using the computational code, the effects of different factors such as: the number of layers, mass flow variation, inlet mass flow rate maldistribution, and stacking pattern on the thermal performance of the heat exchanger have been investigated. The results of this investigation show that when the number of layers for each stream is small, a linear nonuniformity in the mass flow rate of a hot stream has a more destructive effect on the thermal performance than that in a cold stream. Moreover, the heat transfer rate of the heat exchanger is more sensitive to mass flow deviation of cold streams than that of hot streams. In the present research, when the number of unit cells are higher than 15, periodic boundary conditions can be applied to reduce the computational cost.